A Ticket to Ride: The Implications of Direct Intercellular Communication via Tunneling Nanotubes in Peritoneal and Other Invasive Malignancies - Lou, Emil (Frontiers in Oncology, 2020)
It is well established that the role of the tumor microenvironment (TME) in cancer progression and therapeutic resistance is crucial, but many of the underlying mechanisms are still being elucidated. Even with better understanding of molecular oncology and identification of genomic drivers of these processes, there has been a relative lag in identifying and appreciating the cellular drivers of both invasion and resistance. Intercellular communication is a vital process that unifies and synchronizes the diverse components of the tumoral infrastructure. Elucidation of the role of extracellular vesicles (EV) over the past decade has cast a brighter light on this field. Additional niches of intratumoral communication are filled by other modes of intercellular transfer. Tunneling nanotubes (TNTs), tumor microtubes (TMs) and other similar intercellular channels are long filamentous actin-based cellular conduits (in most epithelial cancer cell types, ~15-500 µm in length; 50-1000+ nm in width)(1-4). They extend and form direct connections between distant cells, serving as conduits for direct intercellular transfer of cell cargo, such as mitochondria, exosomes, and microRNAs; however, many of their functional roles in mediating tumor growth remain unknown. These conduits literally create a physical bridge to create a syncytial network of dispersed cells amidst the intercellular stroma-rich matrix. Emerging evidence suggest that they provide a cellular mechanism for induction and emergence of drug resistance and contribute to increased invasive and metastatic potential. They have been imaged in vitro and also in vivo and ex vivo in tumors from human patients as well as animal models, thus not only proving their existence in the TME, but opening further speculation about their exact role in the dynamic niche of tumor ecosystems. TNT cellular networks are upregulated between cancer and stromal cells under hypoxic and other conditions of physiologic and metabolic stress. The field of investigation of TNT-mediated tumor-stromal, and tumor-tumor, cell-cell communication is gaining momentum. If the role of cancer heterocellular signaling via TNTs in the TME is proven to be crucial, then disrupting formation and maintenance of TNTs represents a novel therapeutic approach for ovarian and other similarly invasive peritoneal cancers.